Peranan Sistem Informasi Manajemen Dalam Meningkatkan Kinerja Karyawan Pada Tirta Bina Labuhanbatu - Elvitrianim Purba (Forum Kerjasama Pendidikan Tinggi, 2021)
Management Information System (MIS) is a system that processes and organizes useful data and information to support the implementation of tasks in an organization/company. A company will use information systems to improve / assist employees to support their performance. SIM is very important for the company because its role is very vital or very impactful for the company itself. With the use of SIM companies can have advantages in business processes within the company. Processes in a business that previously did not use a SIM will take a long time. Using SIM will have advantages for the company because business processes can be shortened or simplified. In its use, SIM has a system that can help the performance of employees in the company. So the company does not need to take a long time in some of its business processes